A quasi-experimental study of inquiry learning in hybrid environments: Impact on writing and self-regulated learning levels - Hidayat, Hendi; Yuliasri, Issy; Rukmini, Dwi; Widhiyanto, Widhiyanto (UPT Bahasa Universitas Tanjungpura, 2025)
This study examines the comparative effectiveness of Web-Based Inquiry Learning (WBIL) and Field-Based Inquiry Learning (FBIL) in enhancing academic writing performance among EFL students with differing levels of self-regulated learning (SRL). Sixty third-semester students from UIN Siber Syekh Nurjati Cirebon participated in a quasi-experimental design within a Writing for Academic Purposes course. Students in the WBIL group explored information on Cirebonese wedding ceremonies through online sources, while the FBIL group conducted interviews with cultural figures. Pretest and posttest writing tasks were analyzed using two-way ANOVA. Findings showed that both groups improved, but no statistically significant differences emerged across instructional types or SRL levels. Although the overall model was significant, individual variables did not explain the variance in writing gains. The study contributes by explicitly contrasting online and field inquiry within culturally grounded EFL writing tasks, highlighting that both modes offer equally valuable learning experiences. These findings underscore the importance of authenticity and cultural context in inquiry-based learning and call for further research on how these factors interact with learner characteristics to foster academic writing development. How to cite this paper: Hidayat, H., Yuliasri, I., Rukmini, D., & Widhiyanto, .. (2025). A quasi-experimental study of inquiry learning in hybrid environments: Impact on writing and self-regulated learning levels. Journal of English Language Teaching Innovations and Materials (Jeltim), 7(2), 21-37. http://dx.doi.org/10.26418/jeltim.v7i2.97081